2009
DOI: 10.1016/j.juro.2008.10.165
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Apgar Outcome Score: Perioperative Risk Assessment for Radical Cystectomy

Abstract: In patients undergoing radical cystectomy the surgical Apgar score predicts major postoperative complications and death. This simple and objective postoperative metric may be used to dictate the intensity of care. Prospective studies are needed to determine whether treatment decisions based on this scoring system improve radical cystectomy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…Ito et al [7] demonstrated that patients who underwent renal mass excision were 3.7 times more likely to experience a major complication when the SAS was lower than 4, and 24 times more likely to die within 90 days of surgery as compared to those with a SAS ≥ 8. In patients who underwent radical cystectomy Prasad et al [8] showed a progressive decrease in complications with increasing SAS. We sought to evaluate the practicability of the SAS to predict perioperative adverse events (PAE) of robot-assisted laparoscopic transperitoneal radical prostatectomy (RARP) and open retropubic radical prostatectomy (ORRP) within 30 days of surgery.…”
Section: Introductionmentioning
confidence: 97%
“…Ito et al [7] demonstrated that patients who underwent renal mass excision were 3.7 times more likely to experience a major complication when the SAS was lower than 4, and 24 times more likely to die within 90 days of surgery as compared to those with a SAS ≥ 8. In patients who underwent radical cystectomy Prasad et al [8] showed a progressive decrease in complications with increasing SAS. We sought to evaluate the practicability of the SAS to predict perioperative adverse events (PAE) of robot-assisted laparoscopic transperitoneal radical prostatectomy (RARP) and open retropubic radical prostatectomy (ORRP) within 30 days of surgery.…”
Section: Introductionmentioning
confidence: 97%
“…To date, Gawande's Surgical Apgar Score has been studied in colorectal surgery, vascular surgery, and certain gynecologic and urologic procedures. [7][8][9][10][11] The burgeoning literature on the Surgical Apgar Score also identifies potential weaknesses of the scoring system. For example, calculation of the score relies on EBL, which critics have often tagged as imprecise.…”
mentioning
confidence: 99%
“…Although this score has been validated in selected orthopaedic procedures (10,11,12,13,14) we also wanted to observe the utility of the SAS in the trauma hip fracture surgery patients. Hip fracture surgery repairs are operations of different magnitude.…”
Section: Discussionmentioning
confidence: 99%